Structural metamaterials with negative mechanical/thermomechanical indices - Cardoso, João O. (2022)
Funding Information: This work was funded by National Funds through FCT - Portuguese Foundation for Science and Technology, Reference UID/CTM/50025/2019. Jo?o Cardoso acknowledges the funding by FCT Publisher Copyright: © 2021 Chinese Materials Research Society